L'opposition entre nom et verbe : le problème de l'infinitif - Bulikowski, Brunon (Studia Romanica Posnaniensia, 2005)
In this article the author considers grammatical properties of the infinitive in the French language. Because the French infinitive possesses properties both typical of the verb and of the noun, in order to define its grammatical status it is necessary to mark the boundaries between the two mentioned categories. To illustrate the complexity of this task the author refers to languages in which verbal-nominal opposition differs from that in the French language. Both morphological and syntactic aspects have been here taken into consideration. In the final part of the article the author quotes an interesting theory of G. Guillaume which allows the classification of grammatical categories, the infinitive included, on the basis of the relation of semantic character occurring between them.